Exploratory Action Research: Teaching EFL Vocabulary to Deaf Students through the Use of Visual Aids - González-Reyes, Nicole; Ibáñez-Acevedo, Pamela; Inostroza-Araos, María-Jesús; Strickland, Brandee (Colombian Applied Linguistics Journal, 2021)
In Chile, the 2015 Decree 83 from the Ministry of Education demands curriculum adaptations to ensure that students with special learning needs fully develop their skills by being included into the mainstream classroom. However, little information can be found regarding deaf and hard of hearing (D/HH) students in English as a Foreign Language (EFL) classrooms. Therefore, this qualitative Exploratory Action Research (EAR) aims to explore the contribution of using visual aids in the EFL classroom for teaching written vocabulary to five D/HH students from a public school in Chile. Two multitask tests were conducted before and after the intervention to assess the performance of the students on recalling vocabulary, and a semi structured interview was carried out to identify the students’ perspectives regarding visual aids and EFL learning. While the performance test showed inconclusive results, the students’ perspectives on the use of visual aids were positive. These findings are relevant to provide insights into the challenges these students face and the importance of Sign Language and visual aids to create an effective environment for inclusive teaching practices.